Tradisi Anderenat Dalam Ekologi Budaya: Dinamika Interaksi Manusia Dan Lingkungan - Bahri, Moh. Syaiful; Ghufron, Muhammad (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2025)
This article aims to explore the Anderenat tradition on Gili Iyang Island through the lens of cultural ecology, with the objective of analyzing how local cultural practices function as mechanisms for environmental adaptation and conservation. Employing a qualitative descriptive method and an interpretive framework grounded in cultural ecology theory, the study investigates the embedded values and ecological functions within the Anderenat tradition, particularly in relation to how communities interact with and respond to their natural environment. The findings reveal that Anderenat is not merely a religious or ceremonial activity, but a complex ecological practice that embodies local wisdom transmitted through generations. It integrates spiritual beliefs, social rituals, and environmental actions—such as collective prayers, communal gatherings, and the symbolic planting of coconut trees—as strategic responses to ecological challenges like irregular rainfall and soil infertility. These practices not only reinforce communal solidarity but also cultivate ecological awareness and responsibility among community members. Moreover, the tradition fosters a sense of stewardship over natural resources, contributing to the long-term sustainability of the island’s fragile ecosystem. Theoretically, this study contributes to the discourse on environmental anthropology and cultural ecology by demonstrating how indigenous knowledge systems serve as functional and adaptive responses to environmental change. It suggests that traditions like Anderenat can serve as culturally grounded models for integrating local wisdom with modern scientific approaches in the development of inclusive and sustainable environmental policies